Indoor air quality and psychosocial factors related to sick building syndrome among office workers in new and old buildings of a public university in Klang Valley, Malaysia - Zubir, Nurfarina; Jalaludin, Juliana; Rasdi, Irniza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Sick building syndrome (SBS) has been linked to poor indoor air quality (IAQ) and work-related stress. Objective: This research aims to determine the relationship between environmental and psychosocial factors with SBS among office workers in new and old buildings in Universiti Putra Malaysia, Serdang. Methods: A cross-sectional comparative study was conducted among 120 office workers in new and old buildings in UPM. SBS symptoms and psychosocial factors were identified using validated questionnaires modified from IAQ and work symptoms survey, and Job Content Questionnaire (JCQ). The IAQ parameters measured using IAQ devices. Results: The air velocity, air humidity, temperature and indoor air pollutants level in the new building were significantly higher compared to old building. The prevalence of SBS was significantly higher in the old building compared to the new building (χ2=31.44, p<0.001). There were significant associations between SBS prevalence with temperature (OR=4.02, 95% CI=1.02-15.85), TVOC (OR=4.55, 95% CI=1.12-18.48); UFP (OR=4.63, 95% CI=1.25-17.21); PM2.5 (OR=5.06, 95% CI=1.36-18.89); PM10 (OR=4.80, 95% CI=1.33-17.29) and job insecurity (OR=4.08, 95% CI=1.03-16.23). The findings showed that the indoor air pollutants influenced the old building’s SBS symptoms and job insecurity influenced SBS in the new building after controlling the confounders. Conclusion: The prevalence of SBS among office workers is influenced by indoor air quality and psychosocial factors. Further assessment and preventive steps should be taken to reduce risk factors in the workplace.